The influence of citrus aurantium and caffeine complex versus placebo on the cardiac autonomic response: a double blind crossover design - Brian Kliszczewicz; Emily Bechke; Cassie Williamson; Paul Bailey; Wade Hoffstetter; John McLester; Cherilyn McLester (Taylor & Francis Group, 2018)
Background The purpose of this study was to examine the resting cardiac autonomic nervous system's response to the ingestion of a complex containing Citrus aurantium + Caffeine (CA + C) and its influence on recovery following a high-intensity anaerobic exercise bout in habitual caffeine users. Methods Ten physically active males (25.1 ± 3.9 years; weight 78.71 ± 9.53 kg; height 177.2 ± 4.6 cm; body fat 15.5 ± 3.13%) participated in this study, which consisted of two exhaustive exercise protocols in a randomized crossover design. On each visit the participants consumed either a CA + C (100 mg of CA and 100 mg of C) or placebo (dextrose) capsule. After consumption, participants were monitored throughout a 45-min ingestion period, then completed a repeated Wingate protocol, and were then monitored throughout a 45-min recovery period. Cardiac autonomic function (Heart Rate (HR) and Heart Rate Variability (HRV)) and plasma epinephrine (E) and norepinephrine (NE) were taken at four different time points; Ingestion period: baseline (I1), post-ingestion period (I2); Recovery period: immediately post-exercise (R1), post-recovery period (R2). Heart rate variability was assessed in 5-min increments. Results A repeated measures ANOVA revealed significant time-dependent increases in HR, sympathetic related markers of HRV, and plasma E and NE at I2 only in the CA + C trial (p < 0.05); however, no meaningful changes in parasympathetic markers of HRV were observed. Participants recovered in a similar time-dependent manner in all markers of HRV and catecholamines following the PLA and CA + C trials. Conclusion The consumption of CA + C results in an increase of sympathetic activity during resting conditions without influencing parasympathetic activity. CA + C provides no influence over cardiac autonomic recovery.